Detection of Leptospira species in bat cadavers, Czech and Slovak Republics. Issue 1 (31st December 2022) - Seidlova, Veronika; Straková, Petra; Kejíková, Romana; Nemcova, Monika; Bartonička, Tomáš; Salát, Jiří; Dufková, Lucie; Šikutová, Silvie; Mendel, Jan; McKee, Clifton; Zukal, Jan; Pikula, Jiri; et al.
ABSTRACT: Kidney samples from 300 bat cadavers from the Czech and Slovak Republics were tested for Leptospira DNA using PCR and sequencing of three genes ( lipL32, flab, and 16S ribosomal RNA). Overall detection rate was 4.7% and two bat species ( Myotis myotis and Nyctalus noctula ) were PCR-positive for at least one gene. Detected Leptospira sequences were similar to L. interrogans and L. borgpetersenii, and included a potentially novel species related to L. weilii .